2012
DOI: 10.1111/iju.12037
|View full text |Cite
|
Sign up to set email alerts
|

Japan Cancer of the Prostate Risk Assessment for combined androgen blockade including bicalutamide: Clinical application and validation

Abstract: Objectives The Japan Cancer of the Prostate Risk Assessment was developed as a risk stratification instrument for patients undergoing primary androgen deprivation therapy. However, there have been no studies to validate the accuracy of the Japan Cancer of the Prostate Risk Assessment in predicting clinical outcomes. We examined whether the clinical outcomes of patients treated with combined androgen blockade could be stratified using the Japan Cancer of the Prostate Risk Assessment. Methods A total of 319 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The results showed that the PFS of patients treated with CAB could be stratified by the J-CAPRA score even for a relatively short-term follow-up period, providing good external validation of the J-CAPRA scoring system ( Fig. 3) (11).…”
mentioning
confidence: 82%
“…The results showed that the PFS of patients treated with CAB could be stratified by the J-CAPRA score even for a relatively short-term follow-up period, providing good external validation of the J-CAPRA scoring system ( Fig. 3) (11).…”
mentioning
confidence: 82%
“…1 The validation cohort was retrospectively collected from patients treated in three institutions in Japan. A notable hallmark of the J-CAPRA score is that it is the first prediction model that is applicable to patients receiving hormonal therapy as an initial treatment for prostate cancer with or without metastases.…”
Section: Editorial Comment Editorial Comment To Japan Cancer Of the Pmentioning
confidence: 99%
“…The authors have carried out an external validation of the Japan Cancer of the Prostate Risk Assessment (J-CAPRA) score with a straight forward method in Japanese patients treated with combined androgen blockade therapy using bicalutamide as an initial treatment. 1 The validation cohort was retrospectively collected from patients treated in three institutions in Japan. A notable hallmark of the J-CAPRA score is that it is the first prediction model that is applicable to patients receiving hormonal therapy as an initial treatment for prostate cancer with or without metastases.…”
Section: Editorial Comment To Japan Cancer Of the Prostate Risk Assesmentioning
confidence: 99%
“…9,10 To evaluate prognosis in the high number of advanced disease patients who received primary ADT, the J-CAPRA was designed. [11][12][13][14][15] We attempted to confirm the efficacy of previous risk classifications, and develop a reliable and simple model to predict oncological outcomes in patients who underwent primary ADT.…”
Section: Introductionmentioning
confidence: 99%